Investigation of Determining Factors of Intention and Behavior in Using E-Wallet: Extending The UTAUT-2 Model - Mustafri, Alda; Astuti, Rifelly Dewi (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
This research recommends that considering the current global scenario, it would be greatly beneficial for Indonesia to identify more factors of Behavioral intention and slightly explore this construct in case use electronic wallet. Since the factors underlying decision-making of public to use electronic wallets are relatively less studied, this research will contribute in filling that new void. Most existing studies drew from a single theoretical perspective, which exposes an important gap to be filled with additional research. To this end, the study adapted and extended UTAUT-2 model to account for perceived security as well as epistemic value. This research tested the conceptual model using PLS-SEM analysis with 372 respondents through cross-sectional design and survey methodology. The results indicate the majority of the factors, besides effort expectancy and social influence present a statistically significant relationship with behavioral intentions explaining 63.9% variance such insights have important implications for stakeholders in defining strategic actions to enhance the wider adoption and usage of e-wallet technology, particularly within Indonesia. Keywords: E-Wallet, Extended UTAUT-2, Technology acceptance, Behavioral intention, Consumer behavior